CD44 positive and sorafenib insensitive hepatocellular carcinomas respond to the ATP-competitive mTOR inhibitor INK128 - Badawi, Mohamed (Oncotarget, 2018)
The mTOR pathway is activated in about 50% of patients with hepatocellular carcinoma (HCC). In an effort to identify new pathways and compounds to treat advanced HCC, we considered the ATP-competitive mTOR inhibitor INK128. ATP-competitive mTOR inhibitors attenuate both mTORC1 and mTORC2. INK128 was evaluated in sorafenib sensitive and insensitive HCC cell lines, CD44(low) and CD44(high) HCC and those cell lines with acquired sorafenib resistance. CD44 was significantly increased in Huh7 cells made resistant to sorafenib. Forced expression of CD44 enhanced cellular proliferation and migration, and rendered the cells more sensitive to the anti-proliferative effects of INK128. INK128 suppressed CD44 expression in HCC cells while allosteric mTOR inhibitors did not. CD44 inhibition correlated with 4EBP1 phosphorylation status. INK128 showed better anti-proliferative and anti-migration effects on the mesenchymal-like HCC cells, CD44(high) HCC cells compared to the allosteric mTOR inhibitor everolimus. Moreover, a combination of INK128 and sorafenib showed improved anti-proliferative effects in CD44(high) HCC cells. INK128 was efficacious at reducing tumor growth in CD44(high) SK-Hep1 xenografts in mice when given as monotherapy or in combination with sorafenib. Since the clinical response to sorafenib is highly variable, our findings suggest that ATP-competitive mTOR inhibitors may be effective in treating advanced, CD44-expressing HCC patients who are insensitive to sorafenib.